The NAS Benchmark Kernels for Single and Multi-Tenant Cloud Instances with LXC/KVM - Maliszewski, Anderson Mattheus; Griebler, Dalvan; Schepke, Claudio; Ditter, Alexander; Fey, Dietmar; Fernandes, Luiz Gustavo (2018 International Conference on High Performance Computing Simulation (HPCS), 2018)
Private IaaS clouds are an attractive environment for scientific workloads and applications. It provides advantages such as almost instantaneous availability of high-performance computing in a single node as well as compute clusters, easy access for researchers, and users that do not have access to conventional supercomputers. Furthermore, a cloud infrastructure provides elasticity and scalability to ensure and manage any software dependency on the system with no third-party dependency for researchers. However, one of the biggest challenges is to avoid significant performance degradation when migrating these applications from physical nodes to a cloud environment. Also, we lack more research investigations for multi-Tenant cloud instances. In this paper, our goal is to perform a comparative performance evaluation of scientific applications with single and multi-Tenancy cloud instances using KVM and LXC virtualization technologies under private cloud conditions. All analyses and evaluations were carried out based on NAS Benchmark kernels to simulate different types of workloads. We applied statistic significance tests to highlight the differences. The results have shown that applications running on LXC-based cloud instances outperform KVM-based cloud instances in 93.75% of the experiments w.r.t single tenant. Regarding multi-Tenant, LXC instances outperform KVM instances in 45% of the results, where the performance differences were not as significant as expected.
UnivIS-Import:2019-08-15:Pub.2018.tech.IMMD.IMMD3.thenas
Keywords: cloud computing; parallel processing; virtual machines; virtualisation; multitenant cloud instances; private IaaS clouds; high-performance computing; single node; compute clusters; cloud infrastructure; cloud environment; comparative performance evaluation; scientific applications; multitenancy cloud instances; private cloud conditions; LXC-based cloud instances; KVM-based cloud instances; LXC instances; KVM instances; LXC virtualization technologies; KVM virtualization technologies; LXC-KVM; single tenant cloud instances; performance degradation; NAS benchmark kernels; Cloud computing; Virtualization; Benchmark testing; Containers; Hardware; Kernel; Linux